Pelaksanaan Haji dan Umrah bagi Golongan Khuntha dan Mukhannath - Shahabudin, Razali; Ab Ghani, Anisah (Jurnal Fiqh, 2015)
Gender disorder is one of the factors causing the occurrence of difficulties in implementing obligatory worships such as prayers and the hajj. In this context, the question that often arises is whether that person should be in accordance with the behavior of a man or a woman. The same problem is also faced by individuals who are classified as hermaphrodites (khuntha). This article explains the issues arising in the practice of the hajj and umraa for hermaphrodites and those who suffer from gender disorders. It also proposes a solution to the aboveproblems. This article is a qualitative and library mode research and related data have been analyzed.The article concludes that hermaphrodites shall follow the rules of a woman in performing the hajj and umraa. For the born or intentional transvestites (mukhannath), whether he has or has not undergone sexual transplant operations, or has gone sexual transplant operations without sound syariah ruling,he should follow his or her original sex in observing ritual worships including the hajj and umraa.